The case for major displacement along Nares Strait - Johnson, G. Leonard; Srivastava, Shiri P. (Meddelelser om Grønland. Geoscience, 1982)
Nares Strait is a prominent physiographic lineament between Greenland and Ellesmere Island, Canada. That it has attracted the attention of geologists, geophysicists and geomorphologists is attested to by this volume. This summary is based solely on those articles presented in the volume that suggest that lateral motion has occurred along Nares Strait; the amount of movement indicated for the Strait ranges from 200 to 320 km. The Nares Strait dilemma is not yet resolved. Additional dedicated geophysical and geological investigations in the region surrounding Nares Strait will have to be undertaken before a satisfactory solution to the problem can be found. Hopefully, this volume will instigate such activities.